Innovation of New Knowledge in Sustainable Tourism through Social Innovation (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The goal of our paper is to present the knowledge management process of social innovation endeavour undertaken in the field of sustainable tourism of the capital of Slovenia. We present all phases of social innovation and focus on the findings of the second phase. We use the methodology of social innovation that is composed of structured open-ended questionnaires. Questionnaires took 30-40 minutes to be filled out. The answers were transcribed and analysed with NVivo 10 software. We conclude that social innovation is a beneficial methodology that provides the inclusion of key stakeholders in sustainable tourism. That is, local community has an opportunity to be heard, empowered and engaged in sustainable tourism initiatives and activities that not only enrich the spectre and essence of sustainable tourism offer but also preserve, cultivate and nurture the human potentials of the locals by including and valuing their ideas and creative solutions to social and environmental challenges.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.